Corporate Social Responsibility Disclosure on Tax Avoidance - Lena Herlina (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
This study was conducted to examine the effect of disclosure of corporate social responsibility on tax avoidance. In this study, the disclosure of corporate social responsibility is measured by the GRI-G4 standard. Data were analyzed using simple regression. The population chosen in this study were 55 manufacturing companies in various industrial sectors and the food and beverage sub-sector consumption sector which were listed on the Indonesia Stock Exchange for 4 years in 2015-2018 using the purposive sampling method. In order to obtain a sample of 18 companies that meet the criteria. The results of this study indicate that disclosure of corporate social responsibility has an effect on tax avoidance.